Psychological Distress of The Elderly in Selected Barangays in Caoayan, Ilocos Sur - Bautista, L S F; David, K B; Darisan, LT (PROCEEDING SURABAYA INTERNATIONAL HEALTH CONFERENCE 2019, 2020)
The study determined the level of Psychological Distress of elderly in Selected Barangays in Caoayan, Ilocos Sur CY 2017. It also looked into the relationship between the level of psychological distress and their socio-demographic profile. The following results are: the respondents are 60-66 years old, male, married, lives in poblacion, elementary graduate, nuclear family structure, have a family monthly income of P5,000,with support of family members , roman catholic. The respondents have a “likely to be well” level of psychological distress. A relationship exists between the level of psychological distress and the age, number of family members, educational attainment, family monthly income, family structure, civil status, religion, place of residence and support system of the respondents. It is recommended that: (1) The local government unit should strictly implement RA 9994, an act granting additional benefits and privileges to senior citizens as a program of the government for the elders; (2) The family members should strengthen family ties by giving moral, financial support and to uplift social stability and socio- economic status of the elders; (3) The Senior citizen should actively participate in programs, activities, and gatherings to highlight social support to the organization as long as they can manage.